Experience in a Palliative Care Unit in a Mexican Tertiary Level Hospital - Patricio García-Espinosa (University Library System, University of Pittsburgh, 2022)
Palliative care represents a form of holistic patient care at the end of life, from an emotional, spiritual, biological, and social approach; its ultimate purpose is to enhance human autonomy and dignity and to avoid therapeutic obstinacy. In international literature, there is not many mentions about the role we, undergraduate students, play as part of the palliative care team. It is necessary to be interested in seeking, learning, and understanding palliative care as undergraduate students, and not only the curative medical approach. It is important to emphasize that opioids are important drugs and that we should not be afraid of their use; on the contrary, it is vital to highlight their capacity to alleviate the pain and suffering of a patient and even of a family. When curative treatment is no longer an option, there is always something left for the medical team to do; such as initiating palliative care. I must emphasize that research in this area is still scarce and that the more research and improvement is being made, the more can be done to improve end-of-life care quality. The death of a patient, after all, is a collaborative work between the general physician, the nursing staff, and finally, most importantly, the family. Through this experience, I relate different lessons that I have learned during the first months of my year of medical social service, in the pain and palliative care clinic of the High Specialty Medical Unit #25.